2017
DOI: 10.1097/hcr.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

In-class Active Video Game Supplementation and Adherence to Cardiac Rehabilitation

Abstract: The additional use of AVGs during CR sessions is feasible, safe, and significantly improved daily PA and EE. A dropout reduction trend among its users, which needs to be confirmed in a larger trial, raises awareness to AVG supplementation as a promising strategy to increase CR adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
105
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(116 citation statements)
references
References 13 publications
0
105
0
10
Order By: Relevance
“…Adherence was reported in two different ways: as dropout rates and/or as proportion of sessions/days completed. With respect to dropouts, only three studies 47,53,60 did not lose any participants, while six studies lost between 2.0% and 8.4%, 18,49,51,56‐57,59 three studies lost 12.7%‐17.9%, 55,58,61 one study lost 26.2%, 48 one study lost 28.3%, 50 and one study lost 43.8% 54 of the participants. When considering the proportion of intervention sessions/days attended by the participants, only seven studies reported data, 50‐51,54‐56,60,61 with attendance rates to the exergame intervention being ~30%, 56 62%, 54 63.9%, 60 ~77%, 50,55 and ~84% 51,61 .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Adherence was reported in two different ways: as dropout rates and/or as proportion of sessions/days completed. With respect to dropouts, only three studies 47,53,60 did not lose any participants, while six studies lost between 2.0% and 8.4%, 18,49,51,56‐57,59 three studies lost 12.7%‐17.9%, 55,58,61 one study lost 26.2%, 48 one study lost 28.3%, 50 and one study lost 43.8% 54 of the participants. When considering the proportion of intervention sessions/days attended by the participants, only seven studies reported data, 50‐51,54‐56,60,61 with attendance rates to the exergame intervention being ~30%, 56 62%, 54 63.9%, 60 ~77%, 50,55 and ~84% 51,61 .…”
Section: Resultsmentioning
confidence: 96%
“…The number of participants in the studies varied from 15 60 to 88 52 . Two studies examined exclusively men, 47,50 three exclusively women, 32,51,60 while 11 studies assessed a mixed sex sample 18,48‐49,52‐56,58‐59,61 and one study did not report the participants’ sex 57 . In total, 236 men and 297 women participated in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations